A multinational cohort study of trends in survival following dementia diagnosis - Hao Luo; Marjaana Koponen; Christoph Roethlein; Cornelia Becker; J. Simon Bell; Kebede Beyene; Yi Chai; Amy H. Y. Chan; Celine S. L. Chui; Britta Haenisch; Sirpa Hartikainen; Amy T. Hsu; et al. (Communications Medicine)
Abatract Background Information on the survival of people living with dementia over time and across systems can help policymakers understand the real-world impact of dementia on health and social care systems. This multinational cohort study examines the trends in relative mortality risk following a dementia diagnosis. Methods A common protocol was applied to population-based data from the UK, Germany, Finland, Canada (Ontario), New Zealand, South Korea, Taiwan and Hong Kong. Individuals aged 60+ with an incident dementia diagnosis recorded between 2000 and 2018 were followed until death or the end of the study period. Cox proportional hazards regression was used to assess the association of mortality in dementia patients with the year of dementia diagnosis. Results Data from 1,272,495 individuals, with the mean age at diagnosis ranging from 76.8 years (South Korea) to 82.9 years (Germany), show that the overall median length of survival following recorded diagnosis ranges from 2.4 years (New Zealand) to 7.9 years (South Korea). Hazard ratios (HRs) estimated from Cox proportional hazard models decline consistently over the study period in the UK, Canada, South Korea, Taiwan and Hong Kong, which accounted for 84% of all participants. For example, the HR decreases from 0.97 (95% CI: 0.92–1.02) in 2001 to 0.72 (0.65–0.79) in 2016 in comparison to year 2000 in the UK. Conclusions This study shows a steady trend of decreasing risk of mortality in five out of eight databases, which signals the potential positive effect of dementia plans and associated policies and provides reference for future policy evaluation.